Protein Nanoparticles Made of Recombinant Viral Antigens: A Promising Biomaterial for Oral Delivery of Fish Prophylactics - Thwaite, Rosemary; Ji, Jie; Torrealba, Débora; Coll, Julio; Sabés, Manel; Villaverde, Antonio; Roher, Nerea (Frontiers in Immunology, 2018)
In the search for an eminently practical vaccine strategy for farmed fish, we have devised recombinant viral antigens presented as “nanopellets”. These are inclusion bodies of fish viral antigenic proteins produced in Escherichia. coli. Soluble recombinant proteins are too labile to endure the in vivo environment and maintain full functionality, and therefore require encapsulation strategies. Yet when they are produced as nanostructures, they can withstand high temperatures, gastrointestinal pH and lyophilization. Moreover, these nanomaterials are biologically active, non-toxic to fish, cost effective regarding production and suitable for oral administration. Here we present three versions of nanopellets formed by antigenic proteins from relevant viruses affecting farmed fish: the VNNV coat protein, IPNV viral protein 2 and a VHSV G glycoprotein fragment. We demonstrate that the nanoparticles are taken up in vitro by zebrafish ZFL cells and in vivo by intubating zebrafish as a proof of concept for oral delivery. Encouragingly, analysis of gene expression shows these nanopellets evoke an anti-viral innate immune response in ZFL cells and in rainbow trout head kidney macrophages.